Critical ACE2 Determinants of SARS-CoV-2 and Group 2B Coronavirus Infection and Replication - Lily E. Adams (American Society for Microbiology, 2021)
SARS-CoV-2 (the causative agent of COVID-19) is a major public health threat and one of two related coronaviruses that have caused epidemics in modern history. A method of screening potential infectible hosts for preemergent and future emergent coronaviruses would aid in mounting rapid response and intervention strategies during future emergence events.